Eddy current thickness measurement of nonmagnetic products. Advantages and solution; Неразрушающий контроль: электронное приборостроение, технологии, безопасность; Т. 2 - Belyankov V. Y. (Electrical Engineering and Non-Destructive Testing, 2015)
Заглавие с титульного экрана